Pengaruh Pesan Interaktif Instagram Traveloka terhadap Loyalitas Konsumen Mahasiswa di Kota Solo - Adinda Chintya Dewi; Nieldya Nofandrilla (Universitas Islam Tribakti Lirboyo Kediri, 2026)
The expansion of digital platforms has reconfigured marketing communication, positioning social media interactivity as a key mechanism for cultivating consumer loyalty. While prior studies have examined social media effects broadly, limited attention has been given to how interactive messaging functions as a distinct relational driver within platform-specific contexts. This study addresses this gap by investigating the effect of interactive social media messaging on consumer loyalty through Traveloka’s Instagram account among student consumers in Solo. Grounded in relationship marketing and engagement theory, the study employs a quantitative explanatory design. Data were collected from 100 students using purposive sampling and analyzed through simple linear regression. The findings indicate that interactive messaging exerts a strong and statistically significant positive effect on consumer loyalty (β = 0.913; t = 12.424; p < 0.05), explaining 61.2% of the variance (R² = 0.612). This suggests that interactivity—operationalized through responsiveness, dialogic communication, and participatory content—constitutes a central mechanism in strengthening consumer–brand relationships. The study advances digital marketing scholarship by demonstrating the explanatory power of interactive messaging as a measurable construct and offers practical implications for optimizing Instagram-based communication strategies in the digital travel industry.